LITERARY QUOTATIONS AND THEIR STYLISTIC FUNCTIONS IN THE WORK OF ALISHER NAVOIY - Dosmuxamedova Sevara Boxodir qizi (International Journal of Literature and Language Studies, 2026)
Annotation. The article provides a comprehensive theoretical and practical analysis of intertextuality (intertextual relations) within the framework of modern linguistics, specifically in the fields of text linguistics, linguoculturology, and linguopoetics. The research examines the historical development of the term, tracing its roots from M. Bakhtin's dialogism to J. Kristeva’s formal definition. Special emphasis is placed on N. Fateeva’s classification of intertextual elements, including citations, allusions, and reminiscences. The practical part of the study focuses on the literary heritage of Alisher Navoi, particularly his works such as "Khamsa" and "Tarixi Anbiya wa Hukamo." It demonstrates how the poet masterfully integrated Quranic verses and Hadiths through the art of "iqtibas" (quotation). The author concludes that intertextuality serves as a vital tool for expanding semantic layers and establishing a "cultural dialogue" between the author and the reader.